A simulation study to improve calcium intake through wheat flour fortification - Cormick, Gabriela (2024)
Objective: To simulate the impact on calcium intake – effectiveness and safety – of fortifying wheat flour with 200, 400 and 500 mg of calcium per 100 g of flour. Design: Secondary analysis of cross-sectional data collected through repeated 24 h dietary recalls using the Iowa State University Intake Modelling, Assessment and Planning Program. Setting: Urban cities in the National Health and Nutrition Survey of Argentina (ENNyS 2018–2019). Participants: 21 358 participants, including children, adolescents and adults. Results: Most individuals in all age groups reported consuming wheat flour. The prevalence of low calcium intake was above 80 % in individuals older than 9 years. Simulating the fortification of 500 mg of calcium per 100 g of wheat flour showed that the prevalence of low calcium intake could be reduced by more than 40 percentage points in girls and women aged 19 to less than 51 years and boys and men aged 4 to less than 71 years, while it remained above 65 % in older ages. The percentages above the upper intake level remained below 1·5 % in all age groups. Conclusions: Calcium flour fortification could be further explored to improve calcium intake. Subnational simulations could be performed to identify groups that might not be reached by this strategy that could be explored in Argentina. This analysis could be used to advocate for a strategy to fortify wheat flour.